Entrepreneurial Resiliency: Assessment of Entrepreneurs of Catarman, Northern Samar, Philippines - Legaspi, Korina; Ebdane, Tia Mare; Sanoria, Jane; Formaran, Mar (Journal of Interdisciplinary Perspectives, 2024)
Entrepreneurial resilience is vital for sustaining enterprises, particularly in rural areas where economic instability and natural disasters are prevalent. In the Philippines, where micro, small, and medium enterprises (MSMEs) significantly contribute to economic development, understanding the factors influencing resilience remains underexplored. This study examines entrepreneurial resilience among 111 entrepreneurs in Catarman, Northern Samar, using a descriptive-correlational methodology and quantitative analysis. Data were collected through structured interviews and validated questionnaires. The findings reveal that entrepreneurs possess strong skills in opportunity recognition, creativity, problem-solving, product development, and networking, significantly enhancing resilience. However, limited government support emerged as a key challenge, with no significant relationship found between structural or environmental factors and entrepreneurial resilience. These results highlight the importance of individual entrepreneurial skills in fostering resilience while calling for increased governmental assistance to support rural entrepreneurs. This research addresses a critical gap by focusing on entrepreneurial resilience in a rural context, offering insights for policymakers and stakeholders to develop targeted interventions. By strengthening entrepreneurial skills and improving support systems, the sustainability of MSMEs in economically and environmentally vulnerable regions can be enhanced.